Indicators for high physical strain and overload in elite football players - Meister, S.; Faude, O.; Ammann, T.; Schnittker, R.; Meyer, T. (Scandinavian Journal of Medicine & Science in Sports, 2013)
Laboratory, psychological and performance parameters as possible indicators of physical strain and overload during highly demanding competition phases were evaluated in elite male football players. In two studies with the same objective, periods of high (HE: >270 min during 3 weeks before testing) and low (LE: <270 min) match exposure were compared over the course of an entire season. In study 1 (n=88 players of the first and second German leagues; age: 25.6±4.3 years; body mass index (BMI): 23.2±1.0 kg/m2), blood count, CK, urea, uric acid, CRP and ferritin were determined. In study 2, 19 players of the third German league and the highest under-19 league (age: 19.7±2.8 years; BMI: 22.8±1.7 kg/m2) were screened for individual vertical jump height, maximal velocity and by the Recovery-Stress-Questionnaire for Athletes (REST-Q Sport). The mean differences in exposure times were 180 min (study 1: quartiles: 105, 270 min) and 247 min (study 2: 180, 347 min), respectively. Significant differences were found neither in blood parameters (study 1; P>0.36) nor in physiological testing results or in REST-Q scores (study 2; P>0.20). A 3-week period of high match exposure in elite football players does not affect laboratory, psychometric and performance parameters.